Incidental killing of Sunda clouded leopard in Sarawak, Malaysia - Jayasilan, Mohd. Azlan; Melynda, Cheok Ka Yi; Jack, Liam; Lading, Engkamat; Tisen, Oswald Braken (IUCN/SSC Cat Specialist Group, 2017)
The Sunda clouded leopard Neofelis diardi is listed as Vulnerable on the IUCN Red List and is protected throughout its range. Little is known of its hunting in Sarawak, Malaysia. We conducted an opportunistic survey on the distribution of clouded leopard in Sarawak based on skins and reports of its hunting from 2013 to 2016. We also visited 38 towns and villages during this period. We asked local hunters if they own skins of Sunda clouded leopard and if they could show them to us. Based on this survey, the distribution of Sunda clouded leopard in western Sarawak appears to be patchy. Most of the records showed that the species persists in secondary and primary forest in central and northern Sarawak. Based on skins, a total of nine areas with Sunda clouded leopard presence have been identified. Killing of Sunda clouded leopard was mostly incidental and occasionally in self-defense with little evidence of cross boundary trade.